Heavy metals in water, sediment and three fish species of Dhaleshwari river, Savar - Mohanta, Liton Chandra; Niloy, Md Nazmul Hasan; Chowdhury, Gawsia Wahidunnessa; Islam, Dipa; Lipy, Evena Parvin (Bangladesh Journal of Zoology, 2019)
The study was conducted to assess the pollution of five heavy metals, namely arsenic (As), lead (Pb), cadmium (Cd), chromium (Cr) and copper (Cu). Their concentrations in water and sediments as well as in three fish species such as Labeo rohita (herbivorous), Wallago attu (carnivorous) and Heteropneustes fossilis (omnivorous) were recorded. During wet and dry seasons As, Pb, Cd, Cr, Cu concentrations in river water ranged from the ‘below detection level (BDL)’- 0.0019, 0.3702 - 0.4163, 0.0285 - 0.0294, 1.204 - 1.36, 0.0315 - 0.0807 ppm and 0.0016 - 0.0180, 0.1305 - 0.1889, 0.0297 - 0.0309, BDL, 0.0381 - 0.0543 ppm, respectively. There was no significant seasonal variation in As and Cu conc. in river water but Cr and Pb conc. were significantly higher during the wet season and Cd conc. was significantly higher during dry season. During the wet and dry seasons As, Pb, Cd, Cr, Cu conc. in river sediments ranged from 3.67 - 7.13, 21.58 - 64.96, 1.36 - 1.72, 1126.66 - 1199.46, 45.91 - 115.57 ppm and 5.10 - 8.88, 19.27 - 30.75, 1.39 - 1.48, 99.67 - 446.72, 68.98 - 442.78 ppm, respectively. There were no significant seasonal variations in As, Pb, Cd and Cu concentrations of river sediment but Cr concentration was significantly higher during the wet season. Among muscle, gill and gut tissues of three selected fish species, Pb showed the highest level of accumulation in gill tissues while As showed the lowest level of accumulation in muscle tissues in all three species. Pb, Cd and Cr concentrations in the river water were above WHO Guideline values while As and Cu concentrations were below WHO Guideline values. As, Pb, Cd, Cr and Cu concentrations in the river sediment were above the environmental protection agency’s threshold effect level. In all the three studied fish species, As conc. was below FAO guideline value. Pb, Cd and Cr conc. were higher than FAO guideline value in all three fish species and Cu conc. was above FAO guideline value in one species (H. fossilis). At least three heavy metal concentrations were above FAO guideline value in all three fish species. Therefore, all three fish species were not safe for human consumption. Bangladesh J. Zool. 47(2): 263-272, 2019